Conducting π Columns of Highly Symmetric Coronene, The Smallest Fragment of Graphene. Issue 17 (15th March 2016) - Yoshida, Yukihiro; Isomura, Kazuhide; Kishida, Hideo; Kumagai, Yoshihide; Mizuno, Motohiro; Sakata, Masafumi; Koretsune, Takashi; Nakano, Yoshiaki; Yamochi, Hideki; Maesato, Mitsuhiko; Saito, Gunzi
Abstract: Coronene, which is the smallest D 6 h ‐symmetric polycyclic aromatic hydrocarbon, attracts particular attention as a basic component of electronic materials because it is the smallest fragment of graphene. However, carrier generation by physical methods, such as photo‐ or electric field‐effect, has barely been studied, primarily because of the poor π‐conduction pathway in pristine coronene solid. In this work we have developed unprecedented π‐stacking columns of cationic coronene molecules by electrochemical hole‐doping with polyoxometallate dianions. The face‐to‐face π–π interactions as well as the partially charged state lead to electrical conductivity at room temperature of up to 3 S cm −1, which is more than 10 orders of magnitude higher than that of pristine coronene solid. Additionally, the robust π–π interactions strongly suppress the in‐plane rotation of the coronene molecules, which has allowed the first direct observation of the static Jahn–Teller distortion of cationic coronene molecules. Abstract : Conducting coronene : An unprecedented π‐stacking columns of cationic coronene molecules by electrochemical hole‐doping with polyoxometallate dianions is developed. The face‐to‐face π–π interactions as well as the partially charged state lead to electrical conductivity at room temperature of up to 3 S cm −1, which is more than 10 orders of magnitude higher than that of pristine coronene solid.